Kratom di Indonesia: Dampak Sosial-Ekonomi dan Dilema Kebijakan: Studi Kualitatif - Hasan Ismail; Fidi Setyawan; Gusti Rizaldi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study aims to examine the socio-economic impacts of kratom and identify policy dilemmas based on stakeholder perspectives in Indonesia. A qualitative approach was employed through semi-structured interviews and questionnaires involving seven respondents representing government agencies, non-governmental institutions, and farmers. The data were analyzed to assess perceptions of health benefits, risks of misuse, economic potential, and regulatory challenges. The findings show that kratom is perceived to provide several social benefits, including improved stamina, pain relief, and traditional uses. However, respondents also highlighted risks such as sedation, potential addiction when consumed excessively, and misuse among youth. Economically, kratom is considered to strengthen local income due to its easy cultivation, short harvesting cycle, and promising export opportunities. Nonetheless, unclear legal status has contributed to widespread illegal trade and uncertainty for producers. Most respondents emphasized the need for evidence-based legalization to enhance regulatory oversight, increase state revenue, and provide clarity for communities, although illegal trade may persist without effective enforcement. Overall, the study underscores the importance of a comprehensive policy framework that balances public health protection with the economic value of kratom as an emerging commodity